Ecological Footprints : New development in policy and practice - Collins, Andrea; Flynn, Andrew (Cheltenham Edward Elgar Publishing, 2015)
The ecological footprint is one of the most prominent tools used to measure environmental sustainability, and its rise in academic and policy debates since the early 1990s has been remarkable. Drawing upon research and examples from around the world, the authors critically examine the claims made of the ecological footprint and how it has been applied in practice. This important book provides a unique insight into the ways in which environmental knowledge is used within organisations, and how it is able to carry authority in policy-making processes.
Include Reference and Index
Keywords: Production -- Nature -- Ecology -- Environmental impact analysis--Measurement. -- Sustainable development--Measurement.